Biodiversity of the Gammaridea and Corophiidea (Crustacea: Amphipoda) from the Beagle Channel and the Straits of Magellan: a preliminary comparison between their faunas - L. Chiesa, Ignacio (Universidad de Costa Rica, 2006)
Gammaridea and Corophiidea amphipod species from the Beagle Channel and the Straits of Magellan were listed for the first time; their faunas were compared on the basis of bibliographic information and material collected in one locality at Beagle Channel (Isla Becasses). The species Schraderia serraticauda and Heterophoxus trichosus (collected at Isla Becasses) were cited for the first time for the Magellan region; Schraderia is the first generic record for this region. A total of 127 species were reported for the Beagle Channel and the Straits of Magellan. Sixty-two species were shared between both passages (71.3 % similarity). The amphipod species represented 34 families and 83 genera. The similarity at genus level was 86.4 %, whereas 23 of the 34 families were present in both areas. For all species, 86 had bathymetric ranges above 100 m and only 12 species ranged below 200 m depth. In the Beagle Channel, only one species had a depth record greater than 150 m, whereas in the Straits of Magellan, 15 had such a record. The Beagle Channel and the Straits of Magellan contain 57.5 % of the species, 71 % of the genera and 77.3 % of the families of Gammaridea and Corophiidea from the entire Magellan region.